DAMPAK PEMBERIAN LARUTAN MIKRO ORGANISME LOKAL (MOL) PADA PERTUMBUHAN BUNGA KRISAN INODORUM (CHRYSANTHEMUM INODORUM) DI DESA SUMKARA KABANJAHE - Darnianti Darnianti (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
Local microorganisms can be produced from plant or animal materials. Utilization of local microorganisms has the advantage of being relatively cheap in terms of cost and ease of application is an option that must be implemented by local farmers. The bacteria content in MOL can be used as a starter for composting, biological fertilizer. By using materials available in the environment. The aim of this study was to determine the application of local microorganism (MOL) vegetable MOL on growth and production applied to Inodrum Chrysanthemum cut flowers. Cultivation of cut flower types of Chrysanthemum Inodorum (Chrysanthemum Inodorum) is believed to be able to increase by utilizing local microorganisms (MOL) to maintain soil fertility, increase soil microbial population, maintain environmental sustainability as well as maintain and increase soil productivity (Setianingsih, 2009). This research was conducted in Sumkara Village, located in Karo District, North Sumatra, which is located between Berastagi and Kabanjahe. The community in Sumkara Village is one of the villages that earns an income from Chrysanthemum Inodrum (Chrysanthemum Inodorum) cut flowers. So far the Sumkara people still use chemical pesticides which can damage the soil structure. Many flower growers have complained about the high cost of fertilizers and maintenance for chrysanthemum cut flowers. This research will produce organic liquid fertilizer which is expected to improve soil structure. The focus of this research is the manufacture of MOL and its application for farmers in the Sumkara area. The method used was a completely randomized block design (RAKL). The results of this research will be published in the Accredited Journal indexed by Sinta.